Level of Economic Development and Policies in Mexico and Nigeria (1970-2018): A Comparative Analysis of Growth and Institutions. - Adekanbi, Omolara A.; Vazquez Guzman, David (Sello Editorial Universitario Americana, 2021)
The purpose of this study is to analyse the effects of policies on the economic growth and development in Nigeria and Mexico from the year of the widespread economic crisis, 1970 to 2018, in order to determine the most effective policies especially those that helped Mexico to attain the rank of upper middle income class in the World Bank ranking, and those that have resolved some social problems, such as conflict in Nigeria at some point in time, so they can be adopted by both countries and to recommend new or modified policies. Various economic theories of growth such as Keynesian theory and neoclassical theory were reviewed to select the variables that can affect growth rate of both countries in the regression model that is proposed for data analysis in the methodology. The variables that were studied are interest rate, level of government spending, foreign direct investment, external debt, privatisation, rate of graduates migration, level to estimate their effect on Gross National Income, which is the dependent variable, by using statistical software to calculate those relations, while data is to be gathered, which is average schooling years and policies on education. On the other hand, we also need life expectancy and health policies, the prevalence of undernourishment and agricultural (or food) policies, the level of unemployment and employment policies, level of inequality and poverty and welfare policies, and also casualty rate and policies implemented to curb violence and conflicts, all of this in order to analyse the changes in the rates as a result of the corresponding policies, with the use of principal component analysis when that is suitable.